Prefrontal Gray Matter and Motivation for Treatment in Cocaine-Dependent Individuals with and without Personality Disorders - Moreno-López, Laura; Albein-Urios, Natalia; Martinez-Gonzalez, José Miguel; Soriano-Mas, Carles; Verdejo-García, Antonio (Frontiers in Psychiatry, 2014)
Addiction treatment is a long-term goal and therefore prefrontal-striatal regions regulating goal-directed behaviour are to be associated with individual differences on treatment motivation. We aimed at examining the association between gray matter volumes in prefrontal cortices and striatum and readiness to change at treatment onset in cocaine users with and without personality disorders. Participants included 17 cocaine users without psychiatric comorbidities, 17 cocaine users with Cluster B disorders and 12 cocaine users with Cluster C disorders. They completed the University of Rhode Island Change Assessment Scale, which measures four stages of treatment change (precontemplation, contemplation, action and maintenance) and overall readiness to change, and were scanned in a 3T MRI scanner. We defined three regions-of-interest (ROIs): the ventromedial prefrontal cortex (including medial orbitofrontal cortex and subgenual and rostral anterior cingulate cortex), the dorsomedial prefrontal cortex (i.e., superior medial frontal cortex) and the neostriatum (caudate and putamen). We found that readiness to change correlated with different aspects of ventromedial prefrontal gray matter as a function of diagnosis. In cocaine users with Cluster C comorbidities, readiness to change positively correlated with gyrus rectus gray matter, whereas in cocaine users without comorbidities it negatively correlated with rostral anterior cingulate cortex gray matter. Moreover, maintenance scores positively correlated with dorsomedial prefrontal gray matter in cocaine users with Cluster C comorbidities, but negatively correlated with this region in cocaine users with Cluster B and cocaine users without comorbidities. Maintenance scores also negatively correlated with dorsal striatum gray matter in cocaine users with Cluster C comorbidities. We conclude that the link between prefrontal-striatal gray matter and treatment motivation is modulated by co-existence of personality disorders.